Veteran‐civilian career identity conflict: What is human resource development's role?. Issue 3 (25th August 2020) - Carpenter, Rob E.; Silberman, Dave
Abstract: The United States military is one of the most notable developers of civilian workforce talent. Yet, approximately one third of post 9/11 veterans retain a personal narrative of military identity that they often find conflicts with civilian society—and as a result, with a civilian career. Earlier studies on veteran career transition have emphasized the need to better understand and deconstruct this transition process for human resource development (HRD). Schlossberg's adult transition theory was used to highlight the argument that HRDs role is to reduce transitional barriers and promote transition strategies. Four heuristics are offered as a basis for organizing the HRD practitioners' role in veteran‐civilian career identity conflict: (a) you belong here, (b) you are valued here, (c) you are safe here, and (d) you can thrive here . We close with a discussion for practitioners and future research.